The Impact of Maternal Breastfeeding Knowledge on Breastfeeding Attitudes, Duration and Physical Development of Children - Gurgan, Yasemin; Gomleksiz, Mehtap; Yakar, Burkay (Eurasian Society of Family Medicine, 2025)
Aim: Maternal knowledge is known to influence breastfeeding attitudes, duration, and child development. However, further research is needed to clarify these associations in different populations. This study aimed to examine the relationship between mothers’ breastfeeding knowledge, their attitudes, children’s anthropometric measurements, and breastfeeding duration. Methods: One hundred forty mothers with children aged between 24 and 36 months were enrolled in this study. Participants completed a Sociodemographic Data Form, the Iowa Infant Feeding Attitude Scale, and the Breastfeeding Attitudes Evaluation Scale. Sample size was calculated based on the expected correlation between Iowa Infant Feeding Attitude Scale scores and infant weight gain, yielding a minimum requirement of 140 participants. Results: The mean Iowa Infant Feeding Attitude Scale score of participants was 63.60±6.47. Employed mothers exhibited significantly higher Iowa Infant Feeding Attitude Scale scores compared to non-employed mothers. Mothers who perceived their breastfeeding knowledge as sufficient had significantly higher scores on both the Iowa Infant Feeding Attitude Scale and the Breastfeeding Attitudes Evaluation Scale. There was a significant positive correlation between the total Iowa Infant Feeding Attitude Scale scores and Breastfeeding Attitudes Evaluation Scale scores of participants. Conversely, a significant negative correlation was identified between total Iowa Infant Feeding Attitude Scale scores and the infants' percentage weight change at 0–6 months and 0–12 months. Conclusion: Maternal knowledge and family structure were positively associated with favorable breastfeeding attitudes and longer breastfeeding duration. Family-centered counseling by healthcare professionals, workplace accommodations for employed mothers, and community-based programs should be integrated into public health strategies to promote optimal breastfeeding practices and healthier infant development. © 2025, Eurasian Society of Family Medicine. All rights reserved.
Keywords: attitude; breastfeeding; knowledge; mothers